Strategi Pemasaran Ritel dan Logistik Guna Meningkatkan Kepuasan Konsumen - Ulin Ni'mah Nurhayati; Alfira Putri Sobari; Dewi Utari; Fidya Isroiyatun Khoiriah Arifin; Freya Islamey Zada (Universitas Muhammadiyah Surakarta, 2026)
Logistics and retail marketing are important in building value for customers and increasing customer satisfaction. By conducting this research, it aims to analyze retail marketing strategies and logistics methods to improve marketing effectiveness in achieving customer satisfaction. Using a qualitative approach through a literature review of Philip Kotler and Kevin Lane Keller's books, this research identifies factors such as supply chain management, marketing concepts (7Ps), and customer satisfaction. The results of the study show that the combination of effective retail marketing strategies and efficient logistics can increase customer satisfaction through product availability, delivery time, and proper sales. Therefore, it is hoped that this research can help businesses in implementing marketing strategies that focus on customer satisfaction for the products sold. Keywords: Retail marketing, logistics, customer satisfaction.